Marshaling her heart - Connealy, Mary (Connealy, Mary. Wyoming sunrise, 2023)
"Becky Pruitt has always prided herself on knowing everything that's happening on her successful ranch, so an unexpected admission from her foreman, Nate Paxton, comes as quite a surprise. With the notorious Deadeye Gang on the loose, Nate--a former U.S. Marshal--believes Becky's ranch is the best spot for a group of Marshals to use as a base to hunt them down. The timing couldn't be more crucial for the town of Pine Valley, and Becky feels obligated to help. But after escaping the grasp of her harsh father, she's never liked giving up control, of her life or her ranch. If there's anyone she can trust with her ranch, and her heart, it might be Nate. But the outlaws won't go away quietly, and as danger draws ever nearer, Becky and Nate are faced with impossible choices that will test their growing bond."--Page 4 of cover.